Torque Teno Virus quantification for monitoring of immunomodulation with biologic compounds in the treatment of rheumatoid arthritis. (18th November 2021) - Studenic, Paul; Bond, Gregor; Kerschbaumer, Andreas; Bécède, Manuel; Pavelka, Karel; Karateev, Dmitry; Stieger, Jutta; Puchner, Rudolf; Mueller, Ruediger B; Puchhammer-Stöckl, Elisabeth; Durechova, Martina; Loiskandl, Michaela; et al.
Abstract: Objectives: RA patients who fail to respond to MTX can receive biologic dMARDs (bDMARDs). The Torque Teno Virus (TTV) is a potential novel candidate for monitoring of immunosuppression. We explore TTV in these patients and its association with clinical response to bDMARDs. Methods: The BioBio Study is a multicentre randomized open-label trial, including RA patients with insufficient response to MTX. Patients were randomized to either TNFi (infliximab, INF), anti-IL-6 (tocilizumab, TCZ), CTLA4-Ig (abatacept, ABA) or anti-CD20 (rituximab, RTX) in addition to MTX. PCR was used to quantify TTV in the peripheral blood. Results: TTV was measured in 95 patients (INF, n = 23; TCZ, n = 22; ABA, n = 27; RTX; n = 23). TTV increased by a median of 4.5 × 10 4 copies/ml [c/ml; interquartile range (IQR) 0–7.5 × 10 5 ] after 3 months. TTV levels at month 3 were associated with the Simplified Disease Activity Index (SDAI) ( P = 0.03) and the Clinical Disease Activity Index (CDAI) response ( P = 0.026) at month 6. A TTV cut-off level of 1.2 × 10 6 c/ml at month 3 had a positive likelihood ratio of 2.7 for prediction of an 85% reduction in SDAI at month 6. Conclusion: Our data suggest that TTV levels increase upon TNF, CD20 and costimulation blockade and are associated with the clinical response to bDMARDs in RA patients. Trial registration: ClinicalTrials.gov; https://clinicaltrials.gov ; NCT01638715